Midwifery Care of Newborn Baby Mrs "N" with Low Birth Weight in BLUD Tenriawaru Public Hospital in Class B, Bone Regency - Hasnidar (Jurnal Suara Kesehatan, 2015)
Low Birth Weight (LBW) remains a problem throughout the world, because it is a cause of morbidity and mortality in the neonatal period. The prevalence of LBW is still quite high, especially in countries with low socio-economic. Statistically showed 90% incidence of LBW found in developing countries and the death rate 35 times higher than in infants with a birth weight> 2500 g. This observational study was also conducted interviews with the client's family and midwives related to the client's problem. The author obtained the data by viewing and monitoring directly on the patient. Then physical examination, The author conducted a physical examination of the patient through inspection, palpation, auscultation and percussion systematically from head to toe and laboratory examinations as investigations. Result revealed that data on infant Mrs "N" as a whole is a sign of low birth weight as described in the theory portion of the signs and symptoms experienced by clients that LBW gestational age 37-42 weeks with body weight <2500 grams. The actual problem was LBW which upheld basic diagnostic determination in accordance with the literature. It seems clear that there are similarities between the existing theory with case studies in infants Mrs "N". The low birth weight are very susceptible to hypothermia and nutritional disturbances fulfillment. To sum up, all the actions to be performed on infants Mrs "N" has been planned well to handle a baby with low birth weight as well as the complications that may occur. In the implementation of Midwifery Care in infants Mrs "N" planned action has been fully implemented